New era towards autonomous additive manufacturing: a review of recent trends and future perspectives - Haolin Fan; Chenshu Liu; Shijie Bian; Changyu Ma; Junlin Huang; Xuan Liu; Marshall Doyle; Thomas Lu; Edward Chow; Lianyi Chen; Jerry Ying Hsi Fuh; Wen Feng Lu; et al. (International Journal of Extreme Manufacturing)
The additive manufacturing (AM) landscape has significantly transformed in alignment with Industry 4.0 principles, primarily driven by the integration of artificial intelligence (AI) and digital twins (DT). However, current intelligent AM (IAM) systems face limitations such as fragmented AI tool usage and suboptimal human-machine interaction. This paper reviews existing IAM solutions, emphasizing control, monitoring, process autonomy, and end-to-end integration, and identifies key limitations, such as the absence of a high-level controller for global decision-making. To address these gaps, we propose a transition from IAM to autonomous AM, featuring a hierarchical framework with four integrated layers: knowledge, generative solution, operational, and cognitive. In the cognitive layer, AI agents notably enable machines to independently observe, analyze, plan, and execute operations that traditionally require human intervention. These capabilities streamline production processes and expand the possibilities for innovation, particularly in sectors like in-space manufacturing. Additionally, this paper discusses the role of AI in self-optimization and lifelong learning, positing that the future of AM will be characterized by a symbiotic relationship between human expertise and advanced autonomy, fostering a more adaptive, resilient manufacturing ecosystem.